Steering the nuclear motion in singly ionized argon dimers with mutually detuned laser pulses - Wu, J.; Magrakvelidze, Maia; Vredenborg, A.; Schmidt, L. Ph. H.; Jahnke, T.; Czasch, A.; Dörner, R.; Thumm, Uwe P. E. (My University, 2013)
We demonstrate that the vibrational nuclear motion of singly ionized argon dimers can be controlled with two ultrashort laser pulses of different wavelengths. In particular, we observe a striking ‘‘gap’’ in the pump-probe-delay-dependent kinetic-energy release spectrum only if the probe-pulse wavelength exceeds the pump-pulse wavelength. This ‘‘frustrated dissociation effect’’ is reproduced by our two-state quantum mechanical model, validating its interpretation as a pump-pulse-initiated population transfer between dipole-coupled Born-Oppenheimer electronic states of the dissociating Ar[subscript 2][superscript +] molecular ion. Our numerical results also reproduce the measured collapse and fractional revival of the oscillating Ar[subscript 2][superscript +] nuclear wave packet, and, for single-pulse dissociation, the decrease of the kinetic-energy release with increasing laser wavelength.
Keywords: Singly ionized argon dimers; Laser pulses